Challenges of multilingualism in the EU - Czyżewska, Dorota (Economics and Business Review, 2014)
The paper discusses the challenges of the multilingualism policy in the EU composed of 28 Member States and 24 official and working languages. The aim of the paper is firstly to present multilingualism as the policy in the EU as well as the diversity of EU official languages. Secondly the paper highlights multilingualism as a tool to ensure the smooth functioning of the internal market with the emphasis put on the benefits of multilingualism for European companies. Thirdly challenges resulting from the multilingual policy in the EU are discussed, encompassing in particular translation and interpretation costs, legal implications of translation and interpretation errors, future accession of new EU Member States. (original abstract)